MENINGKATKAN DAYA SAING UMKM MELALUI PENDAFTARAN MEREK: STUDI KASUS DESA PANTAI SEDERHANA, KECAMATAN MUARA GEMBONG, KABUPATEN BEKASI, JAWA BARAT - Gunawan Widjaja (Adiba Aisha Amira, 2024)
The competitiveness of micro, small and medium enterprises through the process of registering a brand can be defined as their ability to improve their competitive position in the market by utilizing the strength of an officially registered brand identity. A registered brand provides legal protection, increases the added value of the product, builds consumer trust, and opens up opportunities to expand a larger market. By having a registered brand, micro, small and medium enterprises can differentiate themselves from competitors, build customer loyalty, and increase bargaining power in business negotiations, which ultimately contributes to increasing overall competitiveness in an increasingly competitive business environment. The research method used in this study uses a literature study. The research findings show that registering a brand has a positive effect on the competitiveness of micro, small and medium enterprises. Some of the benefits obtained include: Increased product added value, Legal protection of intellectual property rights, Increased consumer trust, Ease of expanding the market and Increased bargaining power in business negotiations. Meanwhile, the obstacles faced by micro, small and medium enterprises in the process of registering a brand, such as: Lack of understanding of the importance of brands, Limited access to information and registration procedures, Costs that are considered quite high by some micro, small and medium enterprises and Relatively long processing time. Thus, registering a brand is an important step to increase the competitiveness of micro, small and medium enterprises in Pantai Sederhana Village and has the potential to be implemented in other areas. With the right support from various stakeholders, micro, small and medium enterprises can leverage the power of brands to strengthen their position in an increasingly competitive market.